Service quality, customer satisfaction and loyalty in automobile repair services in Kathmandu - Bist, Sagar Bahadur (Nepalese Journal of Management, 2024)
This study examines the service quality, customer satisfaction and loyalty in automobile repair services in Kathmandu. Customer satisfaction is the dependent variable. The selected independent variables are empathy, tangibility, assurance, responsiveness and reliability. The primary sources of data is used to assess the opinions of respondents regarding empathy, tangibility, assurance, responsiveness and reliability. The study is based on primary data of 121 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of service quality, customer satisfaction and loyalty in automobile repair services in Kathmandu. The study showed a positive impact of empathy on customer satisfaction. It indicates that increasing in empathy leads to change in customer satisfaction. Similarly, tangibility is positively correlated to customer satisfaction. It indicates that better tangibility stimulates the customer satisfaction. Likewise, reliability is positively correlated to customer satisfaction. It indicates that better reliability can stimulates the customer satisfaction. Further, assurance is also positively correlated to customer satisfaction. It indicates that assurance leads to change in customer satisfaction. In addition, responsiveness is positively correlated to customer satisfaction. It indicates that increase in responsiveness leads to change in customer satisfaction.